Structural basis for polyspecificity in the POT family of proton‐coupled oligopeptide transporters. (10th June 2014) - Lyons, Joseph A; Parker, Joanne L; Solcan, Nicolae; Brinth, Alette; Li, Dianfan; Shah, Syed TA; Caffrey, Martin; Newstead, Simon
<x xml:space="preserve">Abstract</x> Mammalian members of the POT family transport both di‐ and tripeptides. This study shows that a bacterial member of this family is able to recognise di‐ and tripeptides in different orientations, explaining this remarkable ligand promiscuity. <boxed-text content-type="graphic" id="embr201338403-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>